The role of MRI in the assessment of polymyositis and dermatomyositis - Tomasová Studynková, J; Charvát, F; Jarosová, K; Vencovsky, J (Rheumatology (Oxford, England), 2007)
OBJECTIVES: Acute inflammation in idiopathic inflammatory myopathies (IIM) causes oedema that can be visualized by magnetic resonance imaging (MRI). The inflammatory infiltrate in IIM is thought to be frequently in a focal distribution. The aim of this study is to better evaluate the relationship of MR image of thigh muscles to clinical and histological parameters in patients with IIM. METHODS: MRI-short tau inversion recovery (STIR) technique was used to distinguish between affected and non-affected muscles. Computer tomography (CT)-controlled targeted needle biopsy was used for sampling. The intensity of muscle oedema, its extent and total assessment on MRI were evaluated with 10 cm visual analogue scale. The intensity of inflammatory infiltrate was assessed using 5-point grading system. The second MRI and muscle biopsy were performed after the time interval of treatment. RESULTS: MR scans, muscle biopsy and clinical examination were performed in 29 patients with polymyositis (PM) and dermatomyositis (DM). Paired MRI-affected and MRI-non-affected biopsy samples were obtained from 17 cases. In six cases, the biopsy was available for comparison before and after period of treatment. At the initial examination, it was the intensity of oedema on MRI that was associated with clinical status. Mean intensity of MRI findings significantly decreased in 10 patients where the MRI was available also after treatment. The mean intensity of inflammatory infiltrate in PM/DM patients was 2.5 +/- 0.7 for MRI-affected and 1.7 +/- 0.6 for MRI-non-affected muscles (P < 0.001). Mean intensity of inflammatory infiltrate in the MRI-affected muscles in the first examination (n = 6) was 2.2 +/- 0.8 and did not significantly decrease in the second examination in samples taken after the treatment (2.0 +/- 0.9). CONCLUSION: It is mainly the signal intensity in MR scan, which is associated with disease activity in the acute presentation of PM/DM. Muscle biopsy guided by positive MRI finding contains significantly more inflammatory cells than the biopsy taken from MRI non-affected sites. However, even in parts of muscles, which look unaffected on MR scan, the inflammatory cells can be found. The intensity on MR scans decreases significantly after the treatment, but the histologically detected inflammation does not change substantially.
Keywords: senioři; jehlová biopsie; Polymyositis; Tomography, X-Ray Computed; výsledek terapie; Biopsy, Needle; Middle Aged; dermatomyozitida; mužské pohlaví; Muscle, Skeletal; Adult; edém; magnetická rezonanční tomografie; Edema; Magnetic Resonance Imaging; ženské pohlaví; Humans; Dermatomyositis; kosterní svaly; lidé středního věku; polymyozitida; dospělí; počítačová rentgenová tomografie; Aged; Female; Treatment Outcome; lidé; Male